METHODOLOGY FOR THE DEVELOPMENT OF PHYSICAL QUALITIES BASED ON THE ANALYSIS OF THE RESULTS OF THE COMPETITION OF YOUNG BELT WRESTLERS: INTERNATIONAL EXPERIMENTS (Innovate Conferences, 2025)
This article covers the methodology of developing the physical qualities of young belt wrestlers based on the analysis of the results of the competition. The study examined international experiments as well as innovative approaches used in foreign countries and analyzed aspects of their effectiveness.nnotation: this article covers the methodology of developing the physical qualities of young belt wrestlers based on the analysis of the results of the competition. The study examined international experiments as well as innovative approaches used in foreign countries and analyzed aspects of their effectiveness. In particular, the methods used in the development of agility, strength, endurance, agility and coordination skills in young athletes were compared in the sports schools of Russia, Japan, Turkey and Korea in the areas of struggle close to belt wrestling. As a result, it was scientifically substantiated that the adaptation of international experiences to national conditions, the improvement of the competition activities of athletes and their ability to increase the level of physical fitness can serve. These approaches are instrumental in increasing the effectiveness of young wrestlers in competitions and achieving sustainable results in the sport.